THE USE FLASH CARD TO IMPROVE YOUNG LEARNER’S VOCABULARY MASTERY - Andriyadi Andriyadi; Apep Nana Irawan (IKIP Siliwangi, 2018)
This paper describes the using of flash cards to improve mastery of the vocabulary of young learners. The purpose of this paper is to illustrate the effectiveness and ineffectiveness of flash cards used in teaching vocabulary for young learners. Researchers conducted research using quantitative methods to elementary school children in SDN 2 Cijenuk. The study was conducted in four steps: first planning action, second implementation, and third observation, and last reflection. Data were collected using quantitative data collection techniques. The results showed that the use of Flashcards can improve the mastery of children's vocabulary. This can be seen from the average value of the test that increased from 71.50 on the previous test to 85.55 in the post-test. Using a flash card can make students pay attention to the lessons well and not make students bored, also makes the learning atmosphere more controllable. Keywords: Vocabulary Mastery, Flash Card, Young Learner